Evaluasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) Berdasarkan HOT-FIT Model di Instalasi Rekam Medis RSUD Kota Mataram - Reni Chairunnisah; Helmina Andriani; Beny Binarto Budi Susilo; Putri Alfarah (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2026)
The Hospital Management Information System (HMIS) is an application of information technology used to improve health services in hospitals. It is important to conduct ongoing evaluations of HMIS performance to identify positive aspects that encourage system use and factors that cause obstacles. Hospitals can develop HMIS by considering user needs and the benefits they obtain. The objective of this study is to evaluate the HMIS in Medical Record Department RSUD Kota Mataram using the HOT-FIT model. The research methodology used in this study is quantitative with a descriptive research design. The population for this study consists of 64 medical records officers. The sampling technique used in this research was total sampling. The analysis results indicate that most respondents rated the system use and organizational structure variables as 'very good', while the user satisfaction, system quality, information quality, service quality, and net benefits variables were rated as 'good'.